ҚАРАҚАЛПАҚ ХАЛҚЫНЫҢ БАТЫРЛАРЫ МИНГЕН ТУЛПАРЛАР ҲАҚҚЫНДА - Оразымбетов, Е.К. (FAN va JAMIYAT, 2024)
The article describes the characteristics of the horses that the Karakalpak heroes rode, their loyalty, friendship and their place in the education of youth from a pedagogical point of view.